Single-ended DC line protection scheme based on first peak time of current-limiting reactor voltage. (August 2023) - Wei, Xiuyan; Zou, Guibin; Chen, Chaochao; Zhang, Shuo; Zhou, Chenghan; Song, Shenglan
Highlights: The protection scheme can operate with high reliability, sensitivity and selectivity even after high-resistance fault occurs. The protection scheme can protect the whole DC line. Protection threshold can be determined independently of simulation. The developed protection prototypes can correctly distinguish the fault section. Abstract: Fast and sensitive DC line protection is an important guarantee for the security of the flexible DC grid. However, the reliability and sensitivity of the DC line protection are greatly affected by the high fault resistance. To overcome this problem, this paper proposes a novel single-ended line protection scheme for multi-terminal flexible DC grid. Firstly, the propagation characteristics of traveling wave after the internal and external faults are analyzed. Furthermore, a single-ended protection criterion based on the first peak time of current-limiting reactor transient voltage is proposed to distinguish the internal and forward external faults, which is independent of simulation. Then, based on the change characteristics of fault component current, a fault direction criterion and fault pole identification criterion are constructed to identify the backward fault and fault pole, respectively. Finally, extensive simulations and experiments show that the proposed protection scheme can identify the fault quickly and sensitively even for the internal remote-end fault with high fault resistance.